Promotion Strategies on the Number of Arrival Guests by the Reception Staff at Sentral Seaview Hotel Penang, Malaysia - Nirwaty Tarigan (Enrichment : Journal of Management, 2021)
Hospitality is one of industry selling a service. One of the people that provide service in the hotel is called as reception staff. He has responsibilities in handling guest check in and checkout including promoting the hotel rooms. The receptionist staff will handle everything the guest order including guest complaints. The receptionist staff will hear nicely the guest complaint and solve the guest problem. After that, the guests who are satisfied to the service then hopefully they will recommend to others. The good experience of the guest will bring them back to stay in the future. This is one of receptionist strategy to promote the hotel product. This research discussed how strategy to promote the hotel product by receptionist, what is the information of the receptionist during promoting the hotel products, how the guest satisfaction about hotel products informed by receptionist in Sentral Seaview Hotel Penang, Malaysia.